(untitled) (Bangladesh Medical Journal, 2019)
Obstructive nephropathy is any affection of the urinary tract characterized by impairment of urine flow through the tract and which, if left untreated, will cause progressive renal damage. Causes in children are congenital or acquired. Congenital causes are pelvi-ureteric junction obstructions, posterior urethral valves (PUV), urethral atresia, phimosis and meatal stenosis. The acquired causes are calculi, post-traumatic and post-inflammatory strictures and meatal stenosis. There are some manifestations like prune-belly syndrome, hydronephrosis and renal failure. Diagnostic investigations include ultrasonography, intravenous urography, cystography and renography. Advanced technologies have impacted on the treatment of the different lesions such as utero vesico-amniotic shunt and endoscopic valve ablation for PUV and minimally invasive techniques for urolithiasis. Nephrectomy may be indicated in a unilateral damaged kidney. Sometimes treatment may fail because of pretreatment irreversible renal damage. Such as end-stage renal failure is an indication for renal transplantation. So, proper treatment is essential to prevent end-stage renal failure. Bangladesh Med J. 2017 Sep; 46 (3): 107-113